New Methods for Processing and Quantifying VO2 Kinetics to Steady State: VO2 Onset Kinetics - McNulty, Craig R.; Robergs, Robert A. (Frontiers in Physiology, 2017)
Current methods of oxygen uptake (VO2) kinetics data handling may be too simplistic for the complex physiology involved in the underlying physiological processes. Therefore, the aim of this study was to quantify the VO2 kinetics to steady state across the full range of sub-ventilatory threshold work rates, with a particular focus on the VO2 onset kinetics. Ten healthy, moderately trained males participated in five bouts of cycling. Each bout involved 10 mins at a percentage of the subject’s ventilation threshold (30, 45, 60, 75, 90%) from unloaded cycling. The VO2 kinetics was quantified using the conventional mono-exponential time constant (tau, τ), as well as the new methods for VO2 onset kinetics. Compared to linear modelling, non-linear modelling caused a deterioration of goodness of fit (main effect, p < 0.001) across all exercise intensities. Remainder kinetics were also improved using a modified application of the mono-exponential model (main effect, p < 0.001). Interestingly, the slope from the linear regression of the onset kinetics data is similar across all subjects and absolute exercise intensities, and thereby independent of subject fitness and τ. This could indicate that there are no functional limitations between subjects during this onset phase, with limitations occurring for the latter transition to steady state. Finally, the continuing use of mono-exponential modelling could mask important underlying physiology of more instantaneous VO2 responses to steady state. Consequently, further research should be conducted on this new approach to VO2 onset kinetics.